The Role of Marketing Management On Image Existence Corporate Institutions - Mohamad Arju Syifa; Afnan Taroqi Fathul Bahari; Misbak Misbak (Return : Study of Management, Economic and Bussines, 2024)
Marketing management is a very important concept in the business world. Marketing management depends on organizational design that is tailored to market needs, especially target markets, in terms of price, distribution from suppliers to customers, and service. However, there are factors that affect the quality of an institution, namely the image of the institution (image). The views, perceptions and assessments of the public towards an institution will also affect the sustainability of the institution. Thus, the purpose of this study is to analyze theories about the role of marketing management on the existence of the image of corporate institutions. The theory used in this study is qualitative research, which is research that does not use quantitative data or statistical measuring tools. In accordance with the object of this research, this type of research is a category of library research, which is a series of studies that use literature studies. The result of his research is that marketing management has a very significant role in shaping the image of the institution. The existence of an institution's image depends on how the corporate institution packages marketing and publicizes it to the public. That marketing management also has a function to shape the company's knowledge and image for the community. Therefore, the existence of the image of the corporate institution depends on how the strategy and management of the company itself.